Towards a Framework for Cognitive-Cultural Offensive Realism: A Psychological Contribution to Understanding the Russo-Ukrainian Conflict - Muperi, James Tauya (Psikoislamika: Jurnal Psikologi Islam, 2025)
While extensive literature exists on offensive realism and state behaviour, a significant gap remains in understanding how cognitive biases and cultural narratives intersect with structural incentives to shape the course of the Russo-Ukrainian conflict. This study introduces a cognitive-cultural offensive realism framework and employs a mixed methods approach, combining discourse analysis, historical process tracing, and game-theoretical modelling, to reveal that Russian strategic decision-making is shaped by material calculations or security dilemmas, and the institutionalisation of historical memory, the operationalisation of psychological predispositions, and the mobilisation of cultural myths in elite discourse. The annexation of Crimea and the escalation in 2022 illustrate how overconfidence, loss aversion, and collective identity narratives can override rationalist expectations, embedding psychological contestation within foreign policy logic. In contrast, Ukrainian resistance and Western responses demonstrate alternative pathways, as each actor recalibrates deterrence, escalation, and alliance-building strategies in response to shifting perceptions of threat and opportunity. Comparative findings demonstrate that the persistence of entrenched narratives and psychological frames in Russian policy has led to recurring miscalculations and fragmented adaptation, rather than seamless strategic coherence, as leaders navigate tensions between historical legitimacy, security imperatives, and evolving international norms. This research identifies three interrelated dynamics: path dependencies sustaining cognitive-cultural patterns in Russian strategic thought; integration of psychological and cultural factors into hybrid warfare; and the complexity of international responses as external actors grapple with unpredictable consequences of identity-driven statecraft. The study’s multi-method design advances theoretical understanding and offers practical insights for policymakers addressing the complex realities of contemporary conflict.